Improving Students' Problem-Solving Ability through Learning Tools Based on Problem Based Learning - Permatasari, C P; Yerizon, Y; Arnawa, I M; Musdi, E (Journal of physics. Conference series, 2020)
Our preliminary research conducted on students grade VII of junior high school showed that the students' mathematical problem-solving ability was still low. We suspected that learning tools used so far have not been able to facilitate students to develop mathematical problem-solving abilities. The low ability to solve mathematical problems of students can be overcome by developing learning tools based on Problem Based Learning. The purpose of this study was to analyse the results of the development of learning tools based on Problem Based Learning to improve the mathematical problem-solving ability of students in grade VII. This type of research is development research where the subjects were students grade VII of junior high school. We used the Plomp model which consists of three stages; investigation, development or prototype, and the assessment. The instruments used to find out the practicality of the learning tools developed were interview guidelines, student questionnaire responses, teacher questionnaire responses, and observation sheets for the implementation of lesson plans. The results showed that our newly developed learning tools have been practical for use in the learning process.